AB0924 The role of self limiting behaviour, depression and sleep in the severity of fatigue in patients with fibromyalgia. (15th June 2017) - Fernandes, M; Guzzo, MP; Iannuccelli, C; Mallia, L; Lucidi, F; Franco, M Di; Violani, C
Abstract : Background: Fatigue and sleep disturbances are prominent symptoms in Fibromyalgia (FM) and significantly affect the level of the patients' impairment. Some studies reported a synergic interaction of depression and poor sleep quality associated with fatigue (e.g. [1]); while Marques et al. [2] showed a significant association of the fatigue severity with a limiting behaviour self-regulatory style of the patients, i.e. reducing daily activities and excessive resting. Objectives: The purpose of this cross-sectional study was to analyse the predictors of severity of fatigue in Italian patients with FM. Methods: Outpatients with a FM diagnosis who fulfilled both ACR/EULAR 1990 and 2010 criteria [3, 4], after a medical visit at the Fibromyalgia center at Sapienza University Hospital "Umberto I", were invited to participate in a study on their cognitions and behaviours wearing for one week a wrist actigraph (AMI Motionlogger Watch). Actigraphic sleep parameters were averaged over six days. After 7 days the participants returned the actigraph and answered a structured interview conducted by a trained psychologist which included validated scales measuring depression (Brief Symptom Inventory [5]), perceived fatigue (Checklist of Individual Strength [6]), sleep habits (Sleep Disorder Questionnaire [7]) and behaviour regulation patterns (All-or-nothing and Limiting behaviour scales from Behavioural Responses to Illness Questionnaire [8]). In the previous month and during the study, pharmacological and non-pharmacological treatments were unchanged. Results: Actigraphic monitoring and structured interview were completed by 39 female FM patients, with a mean age of 44.9 years (SD=8.55) and an illness mean duration of 6.5 years (SD=5.72). The majority of the patients reported insomnia complaints, and 29 (74.4%) met the DSM criteria for chronic insomnia. Fatigue severity resulted as the best subjective measure of fatigue, and was positively and significantly correlated with self-management through limiting behaviour, and with Total Time in Bed (TTB) measured through actigraphy. The correlation between TTB and Total Time Slept (TTS) and depression were not significant. Hierarchical regression considering TTB, Depression and Limiting behaviour, showed that all these variables give a significant independent contribution to the prediction of perceived severity of fatigue (47% of variance): limiting behaviour (β=0.52, p<0.01), TTB (β=0.31, p<0.05), Depression (β=0.29, p<0.05). Conclusions: These correlational findings suggest that self-regulation through limiting activity should be given priority attention in cognitive behavioural interventions aimed at reducing subjective fatigue. References: Nicassio et al. Pain 2002;100:271–9. Marques et al. Int J Behav Med 2013;20:229–38. Wolfe et al. Arthritis Rheum 1990. Wolfe et al. Arthritis Care Res (Hoboken) 2010;62:600–10. Derogatis et al. Pearson; 1993. Beurskens et al. Occup Environ Med 2000;57:353–7. Violani et al. Brain Res Bull 2004;63:415–21. Spence et al. Psychol Med 2005;35:583–93. Disclosure of Interest: None declared